And After Landing Wrong? - Lomanno, Mark (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Mark Lomanno reflects on the impact of Ajay Heble's work—especially the book "Landing on the Wrong Note"—on his life and career.